Meningkatkan Hasil Belajar Siswa Melalui Pendekatan Tematik Dengan Media Gambar Pada Pembelajaran Tema Diri Sendiri Kelas 1 SDN 024 Rambah Samo Tahun Pelajaran 2016/2017 - Maryam Maryam (Indonesian Journal of Basic Education, 2018)
Thematic learning is an integrated learning approach approach that uses themes to link some subjects so as to provide meaningful experiences to learners. One of the appropriate media in this approach is the image media. Media images is one of the media that is not foreign to students. This research is action research which consists of planning, implementation, observation and reflection. This study consists of two cycles consisting of two meetings in each cycle. The focus of this research is learning by using thematic approach with the image media in the students of class I SD Negeri 024 Rambah Samo. The results showed that the students' learning outcomes experienced an increase in the minimum completeness criteria from cycle I to cycle II, namely: cycle 1 (59%) and cycle2 (96%). From the results of the study can be concluded that through thematic approach can improve student learning outcomes of students of Class I SD 024 Rambah Samo Lesson Year 2016/2017